Inhibition of Pseudomonas aeruginosa alginate expression by subinhibitory concentrations of antibiotics - Majtán, V; Hybenová, D (Folia microbiologica, 1996)
The effects of subinhibitory concentrations (1/4, 1/8, 1/16 of the MIC) of quinolones (ciprofloxacin, enoxacin, nalidixic acid, norfloxacin, ofloxacin, pefloxacin), aminoglycosides (amikacin, gentamicin, netilmicin, streptomycin, tobramycin), beta-lactams (aztreonam, ceftazidime, imipenem, ticarcilin) and macrolides (erythromycin, roxitromycin) on the excretion of alginate by a P. aeruginosa strain were studied. Both beta-lactam and macrolide antibiotics were found ineffective at the concentrations tested, except erythromycin and imipenem at 1/4 MIC. Aminoglycosides at a concentration of 1/4 MIC reduced most effectively the excretion of alginate. Quinolones were also effective at this sub-MIC; 1/16 MIC was ineffective with all antibiotics or stimulated the production of alginate.
Keywords: Quinolones; antibakteriální látky; Aminoglycosides; Microbial Sensitivity Tests; Macrolides; makrolidy; Alginates; Pseudomonas aeruginosa; Lactams; Anti-Bacterial Agents; algináty; laktamy; chinolony; mikrobiální testy citlivosti; aminoglykosidy